1993
DOI: 10.2307/3869777
|View full text |Cite
|
Sign up to set email alerts
|

Sex Determination in Flowering Plants

Abstract: In many ways, plants offer unique systems through which to study sex determination. Because the production of unisexual flowers has evolved independently in many plant species, different and novel mechanisms may be operational. Hence, there is probably not one unifying mechanism that explains sex determination in plants. Advances in our understanding of sex determination will come from the analysis of the genetics, molecular biology, and biochemistry of genes controlling sexual determination in plants. Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
94
0
7

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 41 publications
3
94
0
7
Order By: Relevance
“…Dellaporta and Calderon Urrea (1993) conclude that in Cannabis, sex determination must occur very early in the developing flowers. In Mercurialis a similar situation was found, the unisexual flowers being devoid of rudiments of organs of the opposite sex Durand 1991, cited from Dellaporta andCalderon-Urrea 1993).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Dellaporta and Calderon Urrea (1993) conclude that in Cannabis, sex determination must occur very early in the developing flowers. In Mercurialis a similar situation was found, the unisexual flowers being devoid of rudiments of organs of the opposite sex Durand 1991, cited from Dellaporta andCalderon-Urrea 1993).…”
Section: Introductionmentioning
confidence: 94%
“…So far it has not been known which factors are responsible for sex expression in hemp and at which stages the expression of one sex is suppressed or promoted. Mohan Ram andNath (1964, cited from Dellaporta andCalderon-Urrea 1993) found that in C. sativa, male and female flowers differ radically in morphology and size, and show no evidence of the missing sex. Dellaporta and Calderon Urrea (1993) conclude that in Cannabis, sex determination must occur very early in the developing flowers.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another example of PCD in flower development is elimination of sex organ in unisexual flowers. For instance, in maize stamen primordia abort early in development of female flowers [12].Many examples of PCD during normal development of plants described above strongly suggest that plants employ PCD to eliminate some cells or generate specialized cells such as TEs in development. However, at the moment little is known on molecular mechanisms regulating the PCD in plant development.…”
mentioning
confidence: 99%
“…Another example of PCD in flower development is elimination of sex organ in unisexual flowers. For instance, in maize stamen primordia abort early in development of female flowers [12].…”
mentioning
confidence: 99%